2020
DOI: 10.1590/1414-431x20209481
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal formation volume, its subregions, and its specific contributions to visuospatial memory tasks

Abstract: Visuospatial memory (VSM) is the ability to represent and manipulate visual and spatial information. This cognitive function depends on the functioning of the hippocampal formation (HF), located in the medial portion of the temporal cortex. The present study aimed to investigate whether there is an association between the volume of the HF and performance in VSM tests. Highresolution structural images (T1) and neuropsychological tests evaluating VSM were performed on 31 healthy individuals. A VSM index was crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Finally, structural and functional neuroimaging studies have demonstrated an integral role for the hippocampus in learning, remembering, and flexibly navigating spatial information ( 44 48 ). This relationship has been observed bilaterally ( 49 ) and across different subfields ( 47 ). Larger hippocampal volume has been associated with greater navigational experience in taxi drivers ( 50 , 51 ), and both severe hippocampal damage ( 45 ) and CA1 atrophy in patients with multiple sclerosis ( 52 ) are correlated with impaired spatial recall.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Finally, structural and functional neuroimaging studies have demonstrated an integral role for the hippocampus in learning, remembering, and flexibly navigating spatial information ( 44 48 ). This relationship has been observed bilaterally ( 49 ) and across different subfields ( 47 ). Larger hippocampal volume has been associated with greater navigational experience in taxi drivers ( 50 , 51 ), and both severe hippocampal damage ( 45 ) and CA1 atrophy in patients with multiple sclerosis ( 52 ) are correlated with impaired spatial recall.…”
mentioning
confidence: 84%
“…Next, given prior work showing interactions between prenatal exposure to air pollution and ELS on children’s neurodevelopmental outcomes ( 42 ), we hypothesized that greater prenatal PAH exposure would potentiate stress-related reductions in hippocampal volumes. Last, given the effects of air pollution and stress on cognitive development and the role of the hippocampus in visuospatial processing ( 44 49 ), we explored the extent to which hippocampal volume associated with performance IQ (PIQ) scores, as a measure of visuospatial abilities.…”
mentioning
confidence: 99%
“…Some variations of the ATL technique have been described over the years to reduce postoperative neurological deficits: (1) visual field defects due to optic radiation of Meyer’s loop (lower division) that is located on the roof and the lateral wall of the temporal horn of lateral ventricle, thus entering from the lateral cortex, usually a superior quadrantanopia can occur or hemianopsia if the access is too posterior (due to the added injury of the upper division of optic radiation) ( 41–43 ); (2) semantic aphasia consequent to an injury of ventral language network (uncinate, middle and inferior longitudinal, and inferior fronto-occipital fasciculus) in the dominant hemisphere ( 44–48 ); (3) verbal or visuo-spatial memory related to dominant or non-dominant hippocampal total removal, respectively ( 49 , 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although it may have been expected that left hippocampal volume increases might be more closely associated with verbal rather than nonverbal memory changes, prior volumetric studies have also reported an association between left hippocampal volumes and nonverbal memory abilities (Shavitt et al. 2020 ). Overall, the presence of hippocampal volume increase in conjunction with improvement in memory functioning may reflect iTBS induced neuroplasticity within prefrontal-temporal lobe networks.…”
Section: Discussionmentioning
confidence: 99%